The gilt-edged market - Choudhry, Moorad (Butterworth-Heinemann, 2003)
The Gilt-Edged Market is specifically aimed at finance professionals and investors who need to understand the inner working of the United Kingdom gilt market. There is detailed coverage of the different gilt instruments, as well as a look at the structures, institutions and practices of the market itself. Topics include: * Bond basics * Conventional gilts * Index-linked gilts * Gilt strips * The gilt repo market * The gilt bond future basis * Yield spread trading using gilts There are also personal reminiscenes that illustrate the great changes that have occurred in this market since Big Bang, as well as an exposition on the art of trading. The Gilt-Edged Market is ideal reading for traders, salespersons, fund managers, private investors and other professionals involved to any extent in the UK gilt market. * The latest research on index-linked gilts, gilt markets and sterling debt markets presented in an enthusiastic, readable style * Written by gilt-edged market makers and dealers to ensure realistic, practical coverage as well as a clear explanation of the theory, so readers gain from years' experience * Foreword written by Mike Williams, CEO of the Debt Management Office.